FAKTOR – FAKTOR YANG MEMENGARUHI KUALITAS PELAYANAN TERHADAP NASABAH PADA MASA PANDEMI DI BANK SYARIAH - Syam Fitri Nur Cahyani; Muhammad Iqbal Fasa; Suharto (Department of Islamic Banking, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
Islamic banks are banks that run their business by upholding the principles of Islamic law as regulated in the fatwa of the Indonesian Ulema Council (MUI). The principles include justice and balance, benefit, and do not contain elements of usury or objects that are prohibited by Islam. Service quality is an effort to fulfill customer needs and desires and the accuracy of delivery to balance customer expectations. Along with rampant competition, banks are required to maintain the quality of their services, especially in the midst of the covid 19 pandemic. This is done solely to increase customer loyalty. This type of research uses qualitative research. This study generally aims to determine the factors that influence the quality of service to customers during the pandemic at Islamic banks. There are two issues studied in this journal, namely (1) How is the quality of service to customers during the pandemic at Islamic banks. (2) what are the factors that influence the quality of service to customers in Islamic banks.